Review and prospect of supersonic business jet design - Sun, Yicheng; Smith, Howard (Elsevier, 2016)
This paper reviews the environmental issues and challenges appropriate to the design of supersonic business jets (SSBJs). There has been a renewed, worldwide interest in developing an environmentally friendly, economically viable and technologically feasible supersonic transport aircraft. A historical overview indicates that the SSBJ will be the pioneer for the next generation of supersonic airliners. As a high-end product itself, the SSBJ will likely take a market share in the future. The mission profile appropriate to this vehicle is explored considering the rigorous environmental constraints. Mitigation of the sonic boom and improvements aerodynamic efficiency in flight are the most challenging features of civil supersonic transport. Technical issues and challenges associated with this type of aircraft are identified, and methodologies for the SSBJ design are discussed. Due to the tightly coupled issues, a multidisciplinary design, analysis and optimization environment is regarded as the essential approach to the creation of a low-boom low-drag supersonic aircraft. Industrial and academic organizations have an interest in this type of vehicle are presented. Their investments in SSBJ design will hopefully get civil supersonic transport back soon.
Keywords: Supersonic transport; Supersonic business jet; Sonic boom; Aircraft design